2016
DOI: 10.1172/jci.insight.87882
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm in group A streptococcal necrotizing soft tissue infections

Abstract: Necrotizing fasciitis caused by group A streptococcus (GAS) is a life-threatening, rapidly progressing infection. At present, biofilm is not recognized as a potential problem in GAS necrotizing soft tissue infections (NSTI), as it is typically linked to chronic infections or associated with foreign devices. Here, we present a case of a previously healthy male presenting with NSTI caused by GAS. The infection persisted over 24 days, and the surgeon documented the presence of a "thick layer biofilm" in the fasci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
98
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(104 citation statements)
references
References 29 publications
6
98
0
Order By: Relevance
“…In addition, scanning electron microscopy (SEM) revealed that GAS biofilms on MEFs appear in chains within thick and multi-layered aggregates ( Fig. 2B), similar to previous reports of GAS biofilms in vivo (8,12). While JS95 is capable of forming biofilm on polystyrene tissue culture plates (referred hereafter as plastic), biofilms on this abiotic substratum accumulate less biomass compared to biofilms on MEFs, display different developmental kinetics, and have a 3-D architecture distinct from MEF-associated biofilms ( Figs.…”
Section: Gas Forms Biofilms On Mammalian Cellssupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, scanning electron microscopy (SEM) revealed that GAS biofilms on MEFs appear in chains within thick and multi-layered aggregates ( Fig. 2B), similar to previous reports of GAS biofilms in vivo (8,12). While JS95 is capable of forming biofilm on polystyrene tissue culture plates (referred hereafter as plastic), biofilms on this abiotic substratum accumulate less biomass compared to biofilms on MEFs, display different developmental kinetics, and have a 3-D architecture distinct from MEF-associated biofilms ( Figs.…”
Section: Gas Forms Biofilms On Mammalian Cellssupporting
confidence: 88%
“…Antibiotic treatment failure against susceptible clinical GAS isolates has been attributed to biofilm formation, given the increased tolerance of biofilm bacteria to antibiotics (9,10). Indeed, dense clusters of GAS microcolonies have been observed within the soft tissue of NF patients (11) and GAS isolated from human necrotizing soft tissue infections (NSTIs) appeared as multi-layered fibrous biofilms that persisted despite prolonged antibiotic therapy (12). However, despite evidence of biofilm-like communities during GAS infection, most research on the contribution of biofilms to the pathogenesis of GAS disease has been performed in vitro, where infection-associated environments are not fully recapitulated (13).…”
Section: Introductionmentioning
confidence: 99%
“…These are followed by resistance to immune responses, tissue destruction and systemic GAS infection (16). The observation of necrotizing fasciitis biopsy support the in vivo relevance of these results (15). However, questions remain regarding the events occurring during the first hours of infection of the tissues, particularly whenever GAS is in contact with stromal tissues such as the decidua.…”
mentioning
confidence: 87%
“…The current model describing the invasive infections early steps, supported by studies on an infection model of 3D organotypic human skin, suggests adhesion to host tissue, growth, invasion of the tissue within 24 h pi (15). These are followed by resistance to immune responses, tissue destruction and systemic GAS infection (16).…”
mentioning
confidence: 96%
“…This early study demonstrated major hallmarks of many biofilm infections: the presence of a foreign body, which promotes a persistent infection with a low level of inflammation that subsequently leads to tissue destruction. Such were hard to resolve necrotizing soft tissue infections caused by group A Streptococcus pyogenes , usually a rapidly progressing acute infection, recently observed to be associated with in situ biofilm formation, accompanied by a higher bacterial load and an elevated immune response [4]. …”
Section: Diagnosis Of Biofilm Infectionsmentioning
confidence: 99%